A Study in Flow Characteristics of Liquid Falling Film in Spiral Tubes - Zaid A. Abdl-rahman; Ghassan Hamad Abdullah (Tikrit Journal of Engineering Sciences, 2007)
A study has been done on experimental investigation of the flow characteristic of water falling film in spiral tubes. The ratio of the surface film velocity to average film velocity (us/uF) is less than 1 for low angle of inclination (4-8 o) where as it increases as the angle of inclination increases reaching a value of about us/uF = 1.2 . This small value of the velocity ratio is due to the liquid film rotation in coil which causes some deletion. The film thickness (δ) experimental data correlated well bythe following equation:   δ = 0.0048 ReF0.7064 sin-1/3θ ( with R2 = 0.959 )